Science, Technology, Engineering, Mathematic-Based Pure Water Kit: Bibliometric Analysis on Critical Thinking and Environmental Awareness - Dewi Firta Amalia Majid; Endang Susantini; Nafisah Maulidah Rahmah; Muhammad Zahrudin Afnan; Rinaldiyanti Rukmana; Muaz Mohd Zaini Makhtar (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2025)
Critical thinking and environmental awareness are essential 21st-century competencies that need to be developed through integrated science learning approaches. However, studies connecting water purification learning media with educational perspectives remain limited. This study seeks to delineate publication trends, prevailing research themes, and prospective future trajectories concerning the utilization of water purification media in scientific education, specifically in promoting higher-order thinking skills and environmental stewardship within the framework of Sustainable Development Goal 6. This research utilized a bibliometric analysis in accordance with the PRISMA methodology. Data were collected from the Scopus database utilizing the keyword